Red Junglefowl (Gallus gallus) selected for low fear of humans are larger, more dominant and produce larger offspring. (9th June 2014) - Agnvall, B.; Ali, A.; Olby, S.; Jensen, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Many traits associated with domestication are suggested to have developed as correlated responses to reduced fear of humans. Tameness may have reduced the stress of living in human proximity and improved welfare in captivity. We selected Red Junglefowl (ancestors of all domestic chickens) for four generations on high or low fear towards humans, mimicking an important aspect of the earliest period of domestication, and tested birds from the third and fourth generation in three different social tests. Growth and plumage condition, as well as size of eggs and offspring were also recorded, as indicators of some aspects of welfare. Birds selected for low fear had higher weight, laid larger eggs and generated larger offspring, and had a better plumage condition. In a social dominance test they also performed more aggressive behaviour and received less of the same, regardless of whether the restricted resource was feed or not. Hence, dominance appeared to increase as a consequence of reduced fear of humans. Furthermore, egg size and the weight of the offspring were larger in the less fearful birds, and plumage condition better, which could be interpreted as the less fearful animals being better adapted to the environment in which they were selected.